Red rice improvement for human nutrition and abiotic stress tolerance in Madagascar - CGIAR Research Program on Rice (2019)
Promising red rice lines were evaluated in three locations in Madagascar for two seasons and 11 lines were identified for high yield and stress tolerance. Three of the candidates are found to have superior yield advantage (up to 2 t/ha and stress tolerance compared to the local check.